The catalog of magnetic storms for Odessa magnetic anomaly zone - Sobitnyak, L. I.; Ryabov, M. I.; Sukharev, A. L.; Orlyuk, M. I.; Romenets, A. O.; Sumaruk, Yu. P. (Одеські астрономічні публікації, 2018)
On magnetic observatory "Odessa" since 1948 measurements of a magnetic field of Earth . At the same time measurements of three elements of a magnetic field are registered: horizontal component (H), vertical component (Z) and inducement (D). On the basis of these data the catalog of magnetic storms in the 21st century is made. In this release of the catalog during 2000-2009 date and time of the beginning and end of a storm, the storm duration, amplitude on three elements of a magnetic field are specified: H, Z, D, the characteristic of magnetic storms with the indication of the fissile periods. The magnetic station "Odessa" is located near a zone of a magnetic anomaly. For identification of reaction in the nature of the geomagnetic activity arising owing to existence of a magnetic anomaly comparison of geomagnetic disturbances at Odessa and Moscow was carried out.